THE EFFECT OF THE PERFORMANCE-BASED ASSESSMENT STRATEGY ON THE ACHIEVEMENT OF SECOND-GRADE STUDENTS THE AVERAGES SUBJECT IN ARABIC GRAMMAR - Baneen Aqeel Abed, Dr. Mushriq Mohammad Majwai AI-Jubori (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The current research aims to identify the impact of the performance-based assessment strategy on the achievement of the second-grade intermediate students. To achieve this goal, the researcher put the null hypothesis that there is no statistically significant difference at the level (0.05) between the average achievement of the experimental group students who study the Arabic grammar subject according to the performance-based evaluation strategy and the average achievement of the control group students who study the same subject in the traditional method 0 and for verification From that, the researcher relied on an experimental design with partial control, for the two equal experimental and control groups, and she chose a randomized method of medium flasks for girls in the center of Najaf Governorate to be a sample for research. The control group represented (28) students. The researcher conducted parity between the students of the two groups of research in several variables, namely: (the chronological age of the students of the two research groups calculated in months, the academic achievement of the parents, the intelligence test) 0 After the researcher identified the subject that included (6) topics from the Arabic grammar book to be taught to the students of the class The second medium, she formulated behavioral goals that reached (64) behavioral goals and prepared model teaching plans for the subjects to be taught during the experiment. The researcher herself taught the material for both groups, and in order to measure the achievement of the students of the two groups of research in the six topics, she prepared an objective achievement test consisting of (30) paragraphs, (20) paragraphs of the multiple choice type, and (10) paragraphs of the type of supplement, the researcher proved his sincerity and its stability and the discriminatory power of its paragraphs, the difficulty factor and the effectiveness of the wrong alternatives.